![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
计算:(1)(-18)÷214×49÷(-16);(2)4+3×(-2)3+33;(3)-63×(-16)2-72;(4)30÷(15-1
计算:(1)(-18)÷214×49÷(-16);(2)4+3×(-2)3+33;(3)-63×(-16)2-72;(4)30÷(15-16)....
计算:(1)(-18)÷214×49÷(-16);(2)4+3×(-2)3+33;(3)-63×(-16)2-72;(4)30÷(15-16).
展开
1个回答
展开全部
(1)原式=18×
×
×
=
;
(2)原式=4+3×(-8)+27=4-24+27=7;
(3)原式=-63×
-49=-6-49=-55;
(4)原式=30÷
=30×30=900.
4 |
9 |
4 |
9 |
1 |
16 |
8 |
9 |
(2)原式=4+3×(-8)+27=4-24+27=7;
(3)原式=-63×
1 |
62 |
(4)原式=30÷
1 |
30 |
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询